PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE UNTUK MENINGKATKAN HASIL BELAJAR GEOGRAFI - PRIYONO PRIYONO (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2021)
The purpose of this study is to improve geography learning outcomes by applying the Think Pair Share type cooperative learning model in class XII IPS4 SMA N 1 Karangdowo Klaten for the 2019/2020 school year. This research is a classroom action research (Classroom Action Research) which consists of two cycles and each cycle consists of 4 stages, namely planning, implementation, observation and reflection. The research subjects were students of class XII IPS4 at SMA N 1 Karangdowo in the 2019/2020 school year, totaling 34 people. Data collection techniques include observation, learning outcomes tests and documentation. The data analysis used in this study consisted of data reduction, data presentation, conclusion drawing or verification. The data analysis technique of learning outcome scores uses quantitative analysis by using assessments of cognitive, psychomotor and affective aspects of assessment. The results of the research on the application of the Think Pair Share cooperative learning model are as follows: the average score of student learning outcomes at the time of pre-action was 68, which increased by 5% to 73 in the first cycle, and further increased in the second cycle, namely 7% with an average value. 80. In addition, the level of completeness in learning Geography increased, which initially only 47% (16 students) met the KKM, in the first cycle it became 79% (27 students) and the second cycle increased to 94% (32 students). Based on the results of the study, it can be concluded that the application of the Think Pair Share type of cooperative learning method can improve geography learning outcomes for students of class XII IPS4 SMA N 1 Karangdowo, in the 2019/2020 school year. ABSTRAKTujuan dari Penelitian ini untuk meningkatkan hasil belajar geografi dengan penerapan model pembelajaran kooperatif tipe Think Pair Share di kelas XII IPS4 SMA N 1 Karangdowo Klaten tahun pelajaran 2019/2020. Penelitian ini merupakan penelitian tindakan kelas (Classroom Action Research) yang terdiri dari dua siklus dan tiap siklus terdiri dari 4 tahap yaitu perencanaan, pelaksanaan, pengamatan dan refleksi. Subyek penelitian adalah siswa kelas XII IPS4 di SMA N 1 Karangdowo tahun pelajaran 2019/2020 yang berjumlah 34 orang. Teknik pengumpulkan data meliputi observasi, tes hasil belajar dan dokumentasi. Analisis data yang digunakan dalam penelitian ini terdiri dari reduksi data, penyajian data, penarikan kesimpulan atau verifikasi. Teknik analisis data skor hasil belajar menggunakan analisis kuantitatif dengan menggunakan penilaian aspek kognitif, psikomotorik dan penilaian aspek afektif. Hasil penelitian penerapan model pembelajaran kooperatif tipe Think Pair Share adalah sebagai berikut: rata-rata skor hasil belajar siswa pada saat pratindakan sebesar 68 meningkat sebanyak 5% menjadi 73 pada siklus I, dan lebih meningkat pada siklus II yakni 7% dengan nilai rata-rata 80. Selain itu, tingkat ketuntasan belajar Geografi meningkat yang awalnya pada pratindakan hanya 47% (16 siswa) yang memenuhi KKM, pada siklus I menjadi 79% (27 siswa) dan siklus II meningkat menjadi 94% (32 siswa). Berdasarkan hasil penelitian dapat disimpulkan bahwa penerapan metode pembelajaran kooperatif tipe Think Pair Share dapat meningkatkan hasil belajar geografi pada siswa kelas XII IPS4 SMA N 1 Karangdowo, pada tahun pelajaran 2019/2020.